RETRACTED: Ophthalmic Combination of SurR9-C84A and Trichostatin-A Targeting Molecular Pathogenesis of Alkali Burn - Roy, Kislay; Sriramoju, Bhasker; Kanwar, Rupinder K.; Kanwar, Jagat R. (Frontiers in Pharmacology, 2016)
Background: Alkali burn is a frequently occurring ocular injury that resembles ocular inflammation caused by eye allergies, infection, and refractive surgeries. Methods: We investigated the synergistic regenerative potential of dominant negative survivin mutant (SurR9-C84A) and histone deacetylase (HDAC) inhibitor trichostatin-A (TSA) against alkali burn and corneal haze using human keratocytes and rabbit alkali burn model (Female New Zealand white rabbits). Results: Combination of SurR9-C84A and TSA suppressed levels of transforming growth factor (TGF)-β, alpha smooth-muscle actin (α-SMA), fibronectin and HDAC1, leading to apoptosis in myofibroblast cells and, showed the potential to clear the corneal haze. An insult with 0.5 N NaOH for 1 min led to neutrophils infiltration and formation of large vacuoles in the stroma. Treatments with TSA and SurR9-C84A for 40 min led to improvement in the conjunctival and corneal tissue integrity, marked by an increase in clathrin and claudin expressions. An increase in TGF-β and endogenous survivin confirmed wound healing and cell proliferation in rabbit cornea. The blood analysis revealed a substantial decrease in the RBC, WBC, platelets or the haemoglobin content post alkali burn. The cytokine array analysis revealed that NaOH induced expressions of IL-1α and MMP-9, which were found to be significantly downregulated (1.8 and 11.5 fold respectively) by the combinatorial treatment of SurR9-C84A and TSA. Conclusion: Our results confirmed that combination of SurR9-C84A with TSA worked in synergy to heal ocular injury and inflammations due to alkali burn and led to the regeneration of ocular tissue by increasing clathrin, claudin, survivin and TGF-β and reversal of alkali burn by suppressing IL-1α and MMP-9 without inducing haze.